Firdaus Sistem Keamanan Rel Kereta danTraffic Light Untuk Mengurangi Resiko Kecelakaan Berbasis Orange PI - Firdaus; Mardiah Masril; Ondara Eka Putra (Journal of Computer Scine and Information Technology, 2023)
The quality of the meat can be seen from the level of freshness of the meat. The level of freshness of the meat will determine the meat that is suitable for consumption and the meat that is no longer suitable for consumption. There is a lot of public interest in consuming fish and beef, so there are unscrupulous meat sellers who commit fraud by continuing to market meat that is not fresh and even given preservatives so as not to get a loss. Therefore, a system was designed that can detect the level of freshness and formalin in fish and beef. This tool is designed using Arduino Uno, HCHO sensor, MQ 135 sensor, pH sensor,Sensor Ultrasonic, LCD, Buzzer,Water Pump and DC fan. This tool will detect the formalin contained in the meat by using the HCHO sensor if > 1 ppm. Then the ammonia value and pH value were processed using the Fuzzy Logic Tsukamoto method so as to get the level of freshness of the meat